log(x+4)+log(x-4)=log(48)

Simple and best practice solution for log(x+4)+log(x-4)=log(48) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(x+4)+log(x-4)=log(48) equation:


Simplifying
log(x + 4) + log(x + -4) = log(48)

Reorder the terms:
glo(4 + x) + log(x + -4) = log(48)
(4 * glo + x * glo) + log(x + -4) = log(48)
(4glo + glox) + log(x + -4) = log(48)

Reorder the terms:
4glo + glox + glo(-4 + x) = log(48)
4glo + glox + (-4 * glo + x * glo) = log(48)
4glo + glox + (-4glo + glox) = log(48)

Reorder the terms:
4glo + -4glo + glox + glox = log(48)

Combine like terms: 4glo + -4glo = 0
0 + glox + glox = log(48)
glox + glox = log(48)

Combine like terms: glox + glox = 2glox
2glox = log(48)

Reorder the terms for easier multiplication:
2glox = 48glo

Solving
2glox = 48glo

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-48glo' to each side of the equation.
-48glo + 2glox = 48glo + -48glo

Combine like terms: 48glo + -48glo = 0
-48glo + 2glox = 0

Factor out the Greatest Common Factor (GCF), '2glo'.
2glo(-24 + x) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-24 + x)' equal to zero and attempt to solve: Simplifying -24 + x = 0 Solving -24 + x = 0 Move all terms containing g to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + x = 0 + 24 x = 0 + 24 Combine like terms: 0 + 24 = 24 x = 24 Add '-1x' to each side of the equation. x + -1x = 24 + -1x Combine like terms: x + -1x = 0 0 = 24 + -1x Simplifying 0 = 24 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 144=224-w | | 5/400 | | 12.7=0.8x | | 3/2x-5/4x | | (x/4)-(3/2)=(x-7)/2 | | 226=-u+92 | | 11/4s=-11/12 | | 10(2x-5)=18(x+2) | | 56=-8g | | 25x-4.4x+4.6=-69 | | 5y=76 | | 74-x=186 | | 5y-5=76 | | 12t+-8t=-82 | | (7/10)(1/2) | | F(x)=X^3-10x^2+19x+30 | | 2x+10=12x | | 52=-v+272 | | 0x+1y=-4 | | (8/8)(6/3) | | 1y+0x=-4 | | 4b+b-8=12 | | 2005=40x+5000 | | 12t-8t=-82 | | 3/5k=-6/7 | | 24=-5p-7p | | 213-u=143 | | 6-2(3x-1)=14 | | 1x-42=3x+4 | | (8/1)(6/2) | | 1/3p-8-p4 | | (10/5)(2/2) |

Equations solver categories